Crystal structure of the ribosome recycling factor from Escherichia coli - Kim, Kyeong Kyu (Oxford University Press, 2000)
We have determined the crystal structure of the Escherichia coli ribosome recycling factor (RRF), which catalyzes the disassembly of the termination complex in protein synthesis. The L-shaped molecule consists of two domains: a triple-stranded antiparallel coiled-coil and an α/β domain. The coil domain has a cylindrical shape and negatively charged surface, which are reminiscent of the anticodon arm of tRNA and domain IV of elongation factor EF-G. We suggest that RRF binds to the ribosomal A-site through its coil domain, which is a tRNA mimic. The relative position of the two domains is changed about an axis along the hydrophobic cleft in the hinge where the alkyl chain of a detergent molecule is bound. The tRNA mimicry and the domain movement observed in RRF provide a structural basis for understanding the role of RRF in protein synthesis.